the solution is needed fast , help me out
Attachments:
![](https://hi-static.z-dn.net/files/d67/96d64e48ac257780e2d0f04b96ef3dce.jpg)
Answers
Answered by
1
I hope this answer help you
Attachments:
![](https://hi-static.z-dn.net/files/d94/8409c6616c905423eb8a5ab58b6459b1.jpg)
Answered by
1
(a+b+c)³= a³+b³+c³ +3a²(b+c)+3b²(a+c)+3c²(b+a)+6abc
sum of roots
a+b+c=0
sum of product of roots
ab+bc+ca=-5/k
product of roots
abc=-9/k
and we have a³+b³+c³=27
so when we put all the values in the formula
0= 27 -3a³-3b³-3c³ +6(-9/k)
0=27-3(a³+b³+c³) -54/k
54/k=28-3×27
54/k=28-81
54/k=-54
k=-1
HENCE The value of k is -1
sum of roots
a+b+c=0
sum of product of roots
ab+bc+ca=-5/k
product of roots
abc=-9/k
and we have a³+b³+c³=27
so when we put all the values in the formula
0= 27 -3a³-3b³-3c³ +6(-9/k)
0=27-3(a³+b³+c³) -54/k
54/k=28-3×27
54/k=28-81
54/k=-54
k=-1
HENCE The value of k is -1
Vruddhi:
thanks so much
Similar questions